La viande de chien à l’âge du Fer : quels individus pour quelles consommations ? - Marie-Pierre Horard-Herbin (Gallia)
Researches conducted for thirty years on hundreds of sites from the Iron Age regularly uncover dog remains bearing cutting marks, next to food waste from species frequently eaten. However, their frequency is often limited and varies according to the different kinds of settlement, isolated or clustered, sanctuaries or cemeteries. Besides, some dogs escape this common fate, especially in funerary settings where some are cremated and buried with an human being, while others are featured as pieces of meat, mere food offerings. The characteristic of these buried animals – described only by their skeleton –, is their small size which sets them apart from the mob. Trying to define the common consumption of dog meat during the Iron Age ideally needs to link canine morphologies with the context of dog consumption, to find if the form defines the use. To this approach will be added an analysis of the butchery’s operating chain and of the choice of consumpted animals, leading to an attempt to classify this kind of meat, which was probably peculiar.